(untitled) (Książnica Śląska, 2025)
The article aims to outline the issue of the Silesian Uprisings and the Plebiscites in the cinematic output of Kazimierz Kutz as well as discuss them across the spectrum of the director’s worldview evolution, with particular attention to the movie triptych: Sól ziemi czarnej (Salt of the Black Earth), 1969; Perła w koronie (Pearl in the Crown), 1971; Paciorki jednego różańca (The Beads of One Rosary), 1979. Over the years, Kutz completed his initial vision of Uprisings with his theatrical, essayistic and literary works, which clearly imply, even if not the complete revision of his earlier views, the incessant development of critical reflection on the balance of national spurts and the Silesian identity. The author reviews and summarizes the most meaningful representations of this subject by Kazimierz Kutz, the director, the literary man, the publicist.